Zlepki v objektno usmerjenem okolju - Indihar Štemberger, Mojca (Uporabna informatika (Ljubljana), 2000)
Data analysis like Data Mining is getting more and more important every day because the organizations want to get their competitive advantage. Splines arepiecewise polynomial functions that are used for analysis by more Data Mining tools. Besides, they are widely used in CAGD applications for designing. The article presents the object model of splines that is independent of hte concrete application but can serve as basis for any application which uses splines and reduces the gap among such applications andtheir incompatibilty. It has been modeled by standard object-oriented modeling language UML. We also propose saving splines in an ODMG compliant database. In the article the prototype of a system that has been developed in Java is presented as well.
Keywords: analiza podatkov; objektna tehnologija; podatkovno rudarjenje; zlepki